Xófigo vs 177Lu-labelled anti-PSMA - Agostinho, Daniela (2017)
Introduction - PCa (Prostate Cancer) is a disease with a high incidence rate. Xofigo (223Ra dichloride) is a medicine indicated for patients with this disease in the metastatic phase specifically, symptomatic bone metastases. 177Lu-anti-PSMA represents a set of promising molecules in radioimmunotherapy in PCa patients since they are able to recognize PSMA (prostate specific membrane antigen) which is highly expressed in PCa metastases. The objective of this study is to highlight the advantages and disadvantages of both treatments in patients with advanced staged PCa as there are no comparative studies at this time. Methods - The AlSYMPCA study was one of the chosen to analyze since it was what allowed Xofigo to be approved. The phase II study of 177Lu labeled with anti-PSMA with J591 has also analyzed reason being, it is one of the more recent studies with results. Results - Xofigo is currently used in combination with chemotherapy, increasing the survival rate by 3.6 months. The adverse effects associated with this type of treatment are not severe and are reversible. On the other hand, 177Lu-anti-PSMA obtained promising results indicating that it could increase the survival rate up to 21.8 months. It allows simultaneously the acquisition of body images representative of the biodistribution/location of tumors/metastases by their gamma emission and therapeutics since it is also a β- emitter. Conclusions - The study of 177Lu-anti-PSMA molecules has emerged exponentially, being evident to the scientific community the potential in theranostics and radioimmunotherapy techniques, seeking the most appropriate treatment for each type of patient, with the ultimate goal of increasing the survival rate in patients with metastatic prostate cancer.